2011
DOI: 10.1177/1356766711420834
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between domestic and international students’ trip characteristics: Evidence from an Australian university

Abstract: Changes in the demographic structure of a population present opportunities and challenges for the provision of tourism products and services. One such change is the increased participation of domestic and international students in tertiary education that has occurred in many countries over the past 10 years. Despite the research interest in international students' tourism behaviour, to date, few studies have compared domestic with international students. Drawing on the concepts of mobility and diaspora tourism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…It was also revealed that most of the international students had a tendency for travelling during semester breaks, which is in agreement with those of other studies (Field, 1999;Hobson & Josiam, 1993;Jason et al, 2011;Pope, Shanka, & Ali-Knight, 2002) that identified semester breaks as the most preferred time of travelling by international students. The results also revealed that most of the international students tended to stay in hotels followed by friends' house and rented house, while camping was found to be the least selected accommodation among international students, which is in agreement with previous findings identifying hotels and friends' houses as the most preferred accommodation by students (Field, 1999;Glover, 2011;Hsu & Sung, 1997;Kim & Jogaratnam, 2003;Jason et al, 2011;Ryan & Zhang, 2007;Shanka et al, 2001;Weaver, 2003). Staying at hotels as the most preferred accommodation by students during their travels further debunk the common perception that students are more likely to stay in cheaper forms of accommodation such as hostels or backpackers' rooms (Chadee & Cutler, 1996).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It was also revealed that most of the international students had a tendency for travelling during semester breaks, which is in agreement with those of other studies (Field, 1999;Hobson & Josiam, 1993;Jason et al, 2011;Pope, Shanka, & Ali-Knight, 2002) that identified semester breaks as the most preferred time of travelling by international students. The results also revealed that most of the international students tended to stay in hotels followed by friends' house and rented house, while camping was found to be the least selected accommodation among international students, which is in agreement with previous findings identifying hotels and friends' houses as the most preferred accommodation by students (Field, 1999;Glover, 2011;Hsu & Sung, 1997;Kim & Jogaratnam, 2003;Jason et al, 2011;Ryan & Zhang, 2007;Shanka et al, 2001;Weaver, 2003). Staying at hotels as the most preferred accommodation by students during their travels further debunk the common perception that students are more likely to stay in cheaper forms of accommodation such as hostels or backpackers' rooms (Chadee & Cutler, 1996).…”
Section: Resultssupporting
confidence: 93%
“…One of these changes is the increased involvement of overseas students in education that has occurred in numerous countries over the past 10 years (Glover, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Over these years, consumer behavior has also been seeking insights on similarities and differences among various distinctive tourist groups. By employing various market segmentation methods, these studies searched for distinctive group behaviors that reflected mutual travel motivations, aspirations and expectations (Glover, 2011). Most such studies used sociodemographics and lifestyle variables in search of observed choice and/or travel behaviors (Tsiotsou & Goldsmith, 2012).…”
Section: The Consumer Behavior Conceptual Frameworkmentioning
confidence: 99%
“…Tourists' choice of destination and their spatial behavior have been extensively studied over the past three decades (Glover, 2011;Pizam & Mansfeld, 2000). The aim of most studies was to unveil tourists' "push" and "pull" factors and to examine how these factors shape their functional and spatial behavior (Johns & Gyimóthy, 2002;Tsiotsou & Goldsmith, 2012).…”
Section: The Consumer Behavior Conceptual Frameworkmentioning
confidence: 99%
“…There are many studies that examine the variables of academic and socio-cultural adjustment of international students (Berry, 1997;Campbell, 2012;Cownie & Addison, 1996;Gerdes & Mallinckrodt, 1994;Glover, 2011;Li et al, 2009;Yeh & Inose, 2003;Yuan, 2010;Yusoff, 2011;Zhang, 2012). Although the majority of these studies conducted in the United States and European countries, together with increasing the number of international students in Asian countries including Turkey has led to begin researches in this issue (Can, 1996;Otlu, 2010;Özçetin, 2013;Yusoff, 2011;Zhang, 2012).…”
Section: Academic Adjustmentmentioning
confidence: 99%